Positive electrode active material, preparation method thereof and lithium secondary battery containing the same

By forming a coating of carbon-nitrogen bonds and sulfur-oxygen bonds on the surface of lithium metal oxides, the problem of low thermal stability of the positive electrode active material of the ternary NCM system at high temperatures is solved, and the high-temperature life characteristics of lithium secondary batteries are significantly improved. Capacity retention rate, suitable for high energy density applications such as electric vehicles.

CN114631205BActive Publication Date: 2024-12-17POHANG IRON & STEEL CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080066992.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-24
Filing Date
2020-09-23
Publication Date
2024-12-17
Estimated Expiration
2040-09-23

AI Technical Summary

Technical Problem

The existing ternary NCM system positive electrode active materials have low thermal stability at high temperatures, resulting in insufficient high-temperature life characteristics of lithium secondary batteries, and an increase in Ni content will reduce thermal stability.

Method used

The coating with carbon-nitrogen bonds and sulfur-oxygen bonds was formed on the surface of lithium metal oxides, and peaks were observed in the range of 1580cm-1 to 1600cm-1 and 1070cm-1 to 1120cm-1 on the surface of lithium metal oxides, with peaks and average transmittance values, with averaging of transmission, by FT-IR detection, in the range of 1580cm-1 to 1600cm-1 and 1070cm-1 to 1120cm-1. Between 0.990 and 0.998 and 0.985 and 0.993, the decomposition reaction of the electrolyte is suppressed and the high-temperature life characteristics are improved.

Benefits of technology

It significantly improves the high-temperature life characteristics and capacity retention rate of the positive electrode active material, and is suitable for high-energy density lithium secondary batteries, especially electric vehicle applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114631205B_ABST
    Figure CN114631205B_ABST
Patent Text Reader

Abstract

This embodiment relates to a positive electrode active material, a preparation method thereof, and a lithium secondary battery comprising the positive electrode active material. According to one embodiment, a positive electrode active material can be provided, comprising: a lithium metal oxide; and a coating layer located on the surface of the lithium metal oxide, wherein the coating layer comprises a first compound, wherein the first compound has a wavelength of 1580 cm-1 when detected by FT-IR. ‑1 Up to 1600cm ‑1 A peak was observed in the range, and the average value of the transmittance of the peak was 0.990 to 0.998.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material, a preparation method thereof and a lithium secondary battery comprising the same. Background Art

[0002] In recent years, with the explosive growth in demand for IT mobile devices and small electric drive devices (electric bicycles, small EVs, etc.) and the increasing demand for electric vehicles with a range of more than 400 km, research and development of secondary batteries with high capacity and high energy density are actively carried out worldwide.

[0003] In order to prepare such a high-capacity battery, it is necessary to use a high-capacity positive electrode active material.

[0004] Among existing layered cathode active materials, the one with the highest capacity is LiNiO2 (275 mAh / g), but it is prone to structural collapse during charge and discharge, and has low thermal stability due to oxidation number problems, making it difficult to commercialize in practice.

[0005] In order to solve this problem, the unstable Ni sites must be replaced by other stable transition metals (Co, Mn, etc.). For this purpose, a ternary NCM system substituted with Co and Mn was developed.

[0006] However, for the ternary NCM system, the thermal stability decreases as the Ni content increases. Summary of the invention

[0007] Technical issues

[0008] The present embodiment aims to provide a positive electrode active material, in which the decomposition reaction of the electrolyte is suppressed on the surface, thereby improving the high temperature life characteristics.

[0009] Technical Solution

[0010] According to an embodiment of the positive electrode active material, it includes: a lithium metal oxide; and a coating layer, which is located on the surface of the lithium metal oxide, and the coating layer may include a first compound, and the first compound is detected by FT-IR at 1580cm -1 Up to 1600cm -1 A peak was observed in the range, and the average value of the transmittance of the peak was 0.990 to 0.998.

[0011] According to another embodiment of the present invention, a method for preparing a positive electrode active material comprises: preparing a lithium metal oxide; and forming a coating on the surface of the lithium metal oxide, wherein the coating may comprise a first compound having a wavelength of 1580 cm-1 when detected by FT-IR. -1 Up to 1600cm-1 A peak was observed in the range, and the average value of the transmittance of the peak was 0.990 to 0.998.

[0012] Effects of the Invention

[0013] According to the positive electrode active material of one embodiment, a coating containing a compound having a carbon-nitrogen bond is formed on the surface of the lithium metal oxide particles, and this coating is in contact with the electrolyte. Under the action of the compound having a carbon-nitrogen bond contained in the coating, the decomposition reaction of the electrolyte on the positive electrode surface can be suppressed.

[0014] Since the side reactions of the electrolyte are reduced, the high temperature life characteristics of the positive electrode active material can be significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 FT-IR analysis results of the positive electrode active materials prepared according to Examples 1 to 2 and Comparative Example 1.

[0016] Figure 2a to Figure 2c and Figure 3a to Figure 3c 1 is the XPS analysis result of the positive electrode active materials prepared according to Example 1 and Examples 6 to 7.

[0017] Figure 4 The high temperature life characteristics evaluation results of lithium secondary batteries using the positive electrode active materials prepared according to Comparative Example 1 and Examples 1 and 2 are shown. DETAILED DESCRIPTION

[0018] Hereinafter, embodiments of the present invention will be described in detail. However, the following embodiments are examples only, and the present invention is not limited to the embodiments described herein, and the scope of the present invention is subject to the claims.

[0019] A positive electrode active material according to one embodiment includes: a lithium metal oxide; and a coating layer located on a surface of the lithium metal oxide.

[0020] In this embodiment, the coating may include a first compound having a wavelength of 1580 cm -1 Up to 1600cm -1 A peak is observed within the range. In addition, the average transmittance of the peak of the first compound within the wavelength range is 0.990 to 0.998, more specifically 0.993 to 0.995. If the wavelength range and the average transmittance of the peak of the first compound observed during FT-IR detection meet the range, the decomposition reaction of the electrolyte occurring on the surface of the positive electrode active material can be effectively suppressed. Therefore, the high temperature life characteristics of the lithium secondary battery using the positive electrode active material of this embodiment can be significantly improved.

[0021] On the other hand, the coating may further comprise a second compound having a wavelength of 1070 cm -1 Up to 1120cm -1 range, more specifically 1085cm -1 Up to 1105cm -1 A peak is observed in the range. In addition, the average transmittance of the peak of the second compound in the wavelength range is 0.985 to 0.993, more specifically 0.987 to 0.993. If the wavelength range and the average transmittance of the peak of the second compound observed during FT-IR detection meet the range, the decomposition reaction of the electrolyte occurring on the surface of the positive electrode active material can be effectively suppressed. Therefore, the high temperature life characteristics of the lithium secondary battery using the positive electrode active material of this embodiment can be significantly improved.

[0022] When a value obtained by dividing the average absorbance of the first compound by the average absorbance of the second compound is defined as A, A may satisfy the following Formula 1.

[0023] [Formula 1]

[0024] 0.72>A=(average absorbance of the first compound) / (average absorbance of the second compound)>0.41

[0025] More specifically, the A value may be 0.72>A>0.22 or 0.8>A>0.22. If the A value satisfies the range, the decomposition reaction of the electrolyte occurring on the surface of the positive electrode active material can be effectively suppressed. Therefore, the high temperature life characteristics of the lithium secondary battery using the positive electrode active material of this embodiment can be significantly improved.

[0026] For example, the first compound may be a compound having a CN bond.

[0027] For example, the second compound may be a compound having a SOx bond. In this case, the SOx bond may be a SO3 bond or a SO4 bond.

[0028] If a coating layer including the first compound and the second compound as described above is formed on the surface of a lithium metal oxide, a positive electrode active material having suppressed side reactions with an electrolyte and improved high temperature life characteristics can be realized.

[0029] For example, in the spectrum of the coating detected by X-ray photoelectron spectroscopy (XPS), a peak can be observed in at least one of the ranges of 398eV to 404eV, 166eV to 173eV, and 158eV to 166eV. This is the result of the coating containing a compound having a CN bond and / or a compound having a SOx bond.

[0030] The average crystalline size (Lc) of the positive electrode active material is 111 nm to 140 nm, more specifically 115 nm to 120 nm. If the average crystalline size of the positive electrode active material satisfies the above range, the capacity retention rate characteristics at high temperature can be improved.

[0031] On the other hand, the average particle size (D50) of the positive electrode active material according to the present embodiment is 5 μm to 20 μm, and more specifically, may be 10 μm to 20 μm.

[0032] In addition, the specific surface area of ​​the positive electrode active material may be 0.3 to 1.5 m 2 / g, more specifically 0.5 to 1.5 m 2 / g or 0.96 to 1.5 m 2 / g.

[0033] On the other hand, in the present embodiment, the content of nickel in the metal in the lithium metal oxide may be 80 mol % or more. More specifically, for example, the lithium metal oxide may be represented by the following Chemical Formula 1.

[0034] [Chemical formula 1]

[0035] Li x Ni a Co b Mn c M1 d M2 e O2

[0036] In Chemical Formula 1, M1 and M2 are each at least one of Zr, Ti, Mg, Al, Ni, Mn, Zn, Fe, Cr, Mo and W, x is 0.90≤x≤1.07, a is 0.80≤a<1, b is 0<b≤0.3, c is 0<c≤0.3, d is 0<d<0.01, e is 0<e<0.01, and a+b+c+d+e=1.

[0037] At this time, the a is 0.85≤a<1, and more specifically, may be 0.90≤a<1.

[0038] In addition, b may be 0<b≤0.2 or 0<b≤0.1, and c may be 0<c≤0.2 or 0<c≤0.1.

[0039] Meanwhile, M1 is Zr and M2 may be Al. When M1 is Zr and M2 is Al, the positive electrode active material of this embodiment may include 0.05 to 0.6 parts by weight of Zr and 0.01 to 0.4 parts by weight of Al based on the total lithium metal oxide.

[0040] As described in this embodiment, if the nickel content in the metal in the lithium metal oxide is 80% or more, that is, a is 0.80 or more in Chemical Formula 1, a positive electrode active material with high output characteristics can be realized. The positive electrode active material of this embodiment having such a composition has a higher energy density per unit volume, so the capacity of the battery using the positive electrode active material can be increased, and it is suitable for use in electric vehicles.

[0041] A method of preparing a positive electrode active material according to another embodiment may include the steps of preparing a lithium metal oxide and forming a coating layer on a surface of the lithium metal oxide.

[0042] In this case, the coating may include a first compound having a wavelength of 1580 cm-1 when detected by FT-IR. -1 Up to 1600cm -1 A peak was observed within the range of 0.900 to 0.998 in transmittance.

[0043] In addition, the coating may further comprise a second compound having a wavelength of 1070 cm -1 Up to 1120cm -1 A peak was observed in the range, and the average value of the transmittance of the peak was 0.985 to 0.993.

[0044] In this embodiment, the features of the coating are the same as those of the positive electrode active material according to one embodiment described above. Therefore, since the coating has been described in detail in the positive electrode active material according to one embodiment, it will not be repeated in this embodiment.

[0045] The step of preparing the lithium metal oxide may be carried out by conventional methods. For example, as described in the following examples, after preparing the precursor of the lithium metal oxide, it is mixed with the doping raw material, calcined, cooled and pulverized, thereby obtaining the lithium metal oxide.

[0046] Next, a step of forming a coating on the surface of the lithium metal oxide may be performed. At this time, the step of forming the coating may include a step of washing the lithium metal oxide with water. More specifically, the washing step may be performed with a washing solution, and the washing solution includes an additive for forming the coating and water.

[0047] For example, the additive may be at least one of ammonium sulfate, ammonium cobalt sulfate hexahydrate, ammonium nickel sulfate, ammonium manganese sulfate, and ammonium aluminum sulfate.

[0048] The additive in the water washing solution chemically reacts with Li2CO3 dissolved from the lithium metal oxide during washing, and a coating having CN bonds and SO bonds can be formed on the surface of the lithium metal oxide through heat treatment. Therefore, the coating prepared by the same method as in this embodiment contains a compound having a CN bond and / or a compound having a SOx bond, thereby significantly improving the high temperature life characteristics of a battery using a positive electrode active material formed with the coating.

[0049] The content of the additive may be 1 wt % to 7 wt %, more specifically 1 wt % to 5 wt % based on the water washing liquid. If the content of the additive is 1 wt % or more, the high temperature life characteristics can be significantly improved. In addition, if the content of the additive in the water washing liquid is 7 wt % or less, the initial resistance at room temperature is significantly reduced, and the performance of the lithium secondary battery using the positive electrode active material of this embodiment can be further improved.

[0050] In addition, in the water washing process, the content ratio and weight ratio of the lithium metal oxide and the water washing solution may be lithium metal oxide:water washing solution=1:1 to 3:1.

[0051] In this embodiment, after the step of washing the lithium metal oxide with water, the method may further include drying the washed lithium metal oxide and then performing a heat treatment.

[0052] The drying of the washed lithium metal oxide may be performed at a temperature range of 80 to 200° C. for 1 to 30 hours. This is a temperature and time range sufficient to remove moisture and the like remaining on the surface of the positive electrode active material treated with the water washing solution, but is not limited thereto.

[0053] Next, for example, the step of heat treating the washed lithium metal oxide may be performed at a temperature range of 300 to 700° C., more specifically 400 to 600° C., for 3 to 10 hours. In addition, it may be performed in an air (Air), oxygen (O2) or nitrogen (N2) environment. In this embodiment, when the heat treatment temperature satisfies the range, the high temperature life characteristics may be significantly improved.

[0054] Such process conditions are described in more detail in the following examples.

[0055] In another embodiment of the present invention, a lithium secondary battery is provided, which includes: a positive electrode including the positive electrode active material according to one embodiment of the present invention; a negative electrode including the negative electrode active material; and an electrolyte located between the positive electrode and the negative electrode.

[0056] The description of the positive electrode active material is the same as that of the aforementioned embodiment of the present invention, and thus will not be repeated herein.

[0057] The positive active material layer may include a binder and a conductive material.

[0058] The binder plays a role in allowing the positive electrode active material particles to be well bonded to each other and allowing the positive electrode active material to be well bonded to the current collector.

[0059] The conductive material is used to impart conductivity to the electrode, and any conductive material may be used as long as it does not cause chemical changes in the constituted battery.

[0060] The negative electrode includes a current collector and a negative electrode active material layer formed on the current collector, wherein the negative electrode active material layer includes a negative electrode active material.

[0061] As the negative electrode active material, a substance capable of reversibly intercalating / deintercalating lithium ions, lithium metal, an alloy of lithium metal, a substance capable of doping and dedoping lithium, or a transition metal oxide may be used.

[0062] As the substance capable of reversibly inserting and extracting lithium ions, any carbon-based negative electrode active material generally used as a carbon substance in lithium ion secondary batteries can be used, and as a typical example thereof, crystalline carbon, amorphous carbon, or a combination thereof can be used.

[0063] As the alloy of the lithium metal, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and Sn can be used.

[0064] Examples of the substance capable of lithium doping and dedoping include Si, SiO x (0<x<2), Si-Y alloy (the Y is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements and combinations thereof, but not Si), Sn, SnO2, Sn-Y (the Y is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements and combinations thereof, but not Sn), etc.

[0065] Examples of the transition metal oxide include vanadium oxide, lithium vanadium oxide, etc. The negative electrode active material layer also includes a binder and may further include a conductive material.

[0066] The binder plays a role in allowing negative electrode active material particles to be well bonded to each other and allowing the negative electrode active material to be well bonded to the current collector.

[0067] The conductive material is used to impart conductivity to the electrode, and any conductive material may be used as long as it does not cause chemical changes in the constituted battery.

[0068] As the current collector, a material selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer material coated with a conductive metal, and a combination thereof may be used.

[0069] For the negative electrode and the positive electrode, an active material, a conductive material and a binder are mixed in a solvent to prepare an active material composition, and the composition is coated on a current collector to prepare the negative electrode and the positive electrode. Such an electrode preparation method is well known in the art, so a detailed description is omitted in this specification. As the solvent, N-methylpyrrolidone and the like can be used, but it is not limited thereto.

[0070] The electrolyte includes a nonaqueous organic solvent and a lithium salt.

[0071] The nonaqueous organic solvent functions as a medium through which ions participating in the electrochemical reaction of the battery can migrate.

[0072] The lithium salt is a material that functions as a lithium ion source in a battery when dissolved in an organic solvent, thereby ensuring the basic operation of a lithium secondary battery and promoting the migration of lithium ions between a positive electrode and a negative electrode.

[0073] Depending on the type of lithium secondary battery, a separator may also be present between the positive electrode and the negative electrode. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride or a multilayer film of at least two layers thereof may be used, and of course mixed multilayer films such as polyethylene / polypropylene two-layer separators, polyethylene / polypropylene / polyethylene three-layer separators, polypropylene / polyethylene / polypropylene three-layer separators, etc. may be used.

[0074] For lithium secondary batteries, according to the types of separators and electrolytes used, they can be divided into lithium ion batteries, lithium ion polymer batteries and lithium polymer batteries. According to the shape, they can be divided into cylindrical, prismatic, coin and bag types. According to the size, they can be divided into block and film types. The structure and preparation method of these batteries are well known in the field, so they will not be described in detail.

[0075] Hereinafter, embodiments of the present invention will be described in detail. However, the following embodiments are merely examples, and the present invention is not limited to the following embodiments, and the scope of the present invention is subject to the claims.

[0076] (Example 1) Preparation of positive electrode active material containing 88 mol% Ni

[0077] 1) Preparation of positive electrode active material precursor

[0078] NiSO4.6H2O was used as a nickel raw material, CoSO4.7H2O was used as a cobalt raw material, and MnSO4.H2O was used as a manganese raw material. These raw materials were dissolved in distilled water to prepare a 2.5 M aqueous metal salt solution.

[0079] After the coprecipitation reactor was prepared, N2 was purged to prevent oxidation of metal ions during the coprecipitation reaction, and the reactor temperature was maintained at 50°C.

[0080] A metal salt aqueous solution and NH4(OH) as a chelating agent were added to the coprecipitation reactor. In addition, NaOH was used to adjust the pH. The precipitate obtained according to the coprecipitation process was filtered, washed with distilled water, and dried in an oven at 100° C. for 24 hours to prepare a positive electrode active material precursor.

[0081] The components of the prepared precursor are (Ni 0.88 Co 0.095 Mn 0.02 5)(OH)2, average particle size (D50) is 14.8μm.

[0082] 2) Preparation of positive electrode active materials

[0083] Based on 1 mol of the positive electrode active material precursor prepared in 1), 1.05 mol of LiOH·H2O (Sanquan Chemical, battery grade), ZrO2 (Aldrich, 4N) and Al(OH)3 (Aldrich, 4N) were uniformly mixed and mixed to a Zr content of 3400 ppm and an Al content of 280 ppm to prepare a mixture.

[0084] The mixture was placed in a tube furnace and oxygen was introduced to perform calcination, and then cooled to room temperature and pulverized to prepare calcined body powder.

[0085] Next, for the water washing process, 1 g of ammonium sulfate was added to 100 g of distilled water (DI water) and stirred for 1 minute to prepare a water washing solution.

[0086] 100 g of the calcined powder was added to the water washing solution and stirred for 10 minutes, and then filtered. After washing, the filtered calcined powder was dried in a chamber above 100° C., and then heat-treated in an oxygen environment at a temperature of 400° C. for 3 hours to finally obtain a positive electrode active material.

[0087] (Examples 2 to 7, Comparative Example 1 and Reference Examples 1 to 2)

[0088] A positive electrode active material was prepared by the same method as in Example 1 except that the heat treatment conditions of the water washing liquid component and the calcined body powder filtered after water washing were adjusted as shown in Table 1 below.

[0089]

Table 1

[0090]

[0091] (Experimental Example 1) FT-IR (Fourier Transform Infrared Spectroscopy) Analysis

[0092] The positive electrode active materials prepared according to Examples 1 to 2 and Comparative Example 1 were analyzed by FT-IR (Fourier transform infrared spectroscopy), and the results are shown in Figure 1 middle.

[0093] See also Figure 1 The results of Examples 1 and 2 show that at 1580 cm -1 Up to 1600cm -1 The transmittance decreases as the content of ammonium sulfate increases in the wavelength region. In addition, at 1070 cm where S=O symmetric stretch is present, -1 Up to 1120cm -1 The wavelength region is also the same, the more the content of ammonium sulfate increases, the lower the transmittance. In this way, when the content of ammonium sulfate increases and the transmittance detected in the coating of the positive electrode active material decreases, the high temperature life characteristics of the lithium secondary battery can be greatly improved.

[0094] On the other hand, in the case of the positive electrode active material prepared according to Comparative Example 1 which was subjected to the water washing process with distilled water only without forming a coating layer as in Comparative Example 1, the -1 Up to 1600cm -1 The peak is observed in the wavelength region, but at 1070 cm -1 Up to 1120cm -1 Almost no peak is observed in the wavelength region.

[0095] (Experimental Example 2) XPS (X-ray Photoelectron Spectroscopy) Analysis

[0096] The positive electrode active materials prepared according to Example 1 and Examples 6 to 7 were analyzed by XPS (X-ray photoelectron spectroscopy), and the results are shown in Figure 2a to Figure 2c and Figure 3a to Figure 3c middle.

[0097] See also Figure 2a to Figure 2c , the Nls peak at around 400.5 eV is observed to be a CN bond state. In addition, see Figure 3a to Figure 3c, the S2p peak near 170.2 eV was observed to be a SOx (x: 3-4) bond state. Therefore, the positive electrode active material according to the present embodiment contains a compound having a CN bond and a compound having a SOx bond in the coating layer.

[0098] (Experimental Example 3) Detection of the average particle size of the positive electrode active material

[0099] For the positive electrode active materials prepared according to Comparative Example 1, Examples 1 to 7 and Reference Examples 1 to 2, the average particle size (D50, μm) was measured using a particle size analyzer, and the results are shown in Table 2 below.

[0100] (Experimental Example 4) Detection of the specific surface area of ​​the positive electrode active material

[0101] For the positive electrode active materials prepared according to Comparative Example 1, Examples 1 to 4 and Reference Examples 1 to 2, the specific surface areas were measured using a BET detector (QuantaChrome, Autosorb-iQ / MP), and the results are shown in Table 2 below.

[0102] (Experimental Example 5) XRD (X-ray Diffraction) Analysis

[0103] For the positive active materials prepared according to Comparative Example 1, Examples 1 to 7, and Reference Examples 1 to 2, the crystalline size was measured by X-ray diffraction measurement using CuKα rays and is shown in Table 2 below.

[0104] As shown in Table 2 below, the average crystal size of the positive electrode active materials according to Examples 1 to 4 satisfies the range of 111 nm to 140 nm.

[0105] (Experimental Example 6) Evaluation of electrochemical characteristics

[0106] Electrochemical evaluation was performed after preparing 2032 coin-type half cells using the positive electrode active materials prepared according to Comparative Example 1, Examples 1 to 7, and Reference Examples 1 to 2.

[0107] (1) Preparation of coin-type half-cell

[0108] Specifically, the positive electrode active material, polyvinylidene fluoride binder (trade name: KF1100) and Denka black conductive material are mixed in a weight ratio of 92.5:3.5:4, and the mixture is added to N-methyl-2-pyrrolidone (N-Methyl-2-pyrrolidone) solvent, and the solid content in the solvent reaches about 30 weight % to prepare a slurry of the positive electrode active material.

[0109] The slurry was coated on an aluminum foil (thickness: 15 μm) as a positive electrode collector using a doctor blade, and then pressed after drying to prepare a positive electrode. The positive electrode loading was about 14.6 mg / cm 2 , the compression density is about 3.1g / cm 3 .

[0110] A 2032 coin-type half-cell was prepared by conventional methods using the positive electrode, a lithium metal negative electrode (thickness of 200 μm, Honzo metal), an electrolyte and a polypropylene separator. The electrolyte was prepared by dissolving 1M LiPF6 in a mixed solvent of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate (EMC) (mixing ratio of EC: DMC: EMC = 3: 4: 3 volume %), and adding 1.5 wt% of vinylene carbonate (VC) thereto.

[0111] (2) Evaluation of 45°C high temperature cycle characteristics

[0112] The coin-type half-cell prepared in (1) was aged at room temperature (25° C.) for 10 hours and then subjected to a charge and discharge test.

[0113] For capacity evaluation, 215 mAh / g was used as the reference capacity, and the charge and discharge conditions were CC / CV2.5-4.25 V, 1 / 20 C cut-off. For initial capacity, it was carried out under 0.2C charge / 0.2C discharge conditions. For high temperature cycle life characteristics, after 50 tests at high temperature (45°C) under 0.5C charge / 0.5C discharge conditions, the retention rate of the 50th capacity relative to the first capacity is shown in Figure 4 and Table 2 below.

[0114] See Table 2 and Figure 4 It can be seen that in the case of Examples 1 and 2 where a coating layer having CN bonds and S0x (x: 3-4) bonds exists on the surface of the positive electrode active material, the high temperature cycle life is significantly increased compared to Comparative Example 1 where such a coating layer is not formed.

[0115] (3) Evaluation of initial DC resistance characteristics at room temperature at 25°C

[0116] The coin-type half-cell prepared in (1) was aged at room temperature (25° C.) for 10 hours and then subjected to a charge and discharge test.

[0117] For capacity evaluation, 215 mAh / g was used as the reference capacity, and the charge and discharge conditions were CC / CV2.5-4.25 V, 1 / 20 C cut-off. For initial capacity, it was carried out under 0.2 C charge / 0.2 C discharge conditions. For room temperature initial DC resistance, the voltage change within 60 seconds after applying a 0.2 C discharge current was detected when charging to 100% at 0.2 C and 4.25 V, and the room temperature initial DC resistance was calculated and shown in Table 2.

[0118] As shown in Table 2, compared with Comparative Example 1 in which no additive was used in the water washing process, the initial resistance at room temperature of Examples 1 to 7 and Reference Examples 1 and 2 in which the additive was used to prepare the positive electrode active material in the water washing process was significantly reduced. In particular, in the case of the positive electrode active materials of Examples 1 to 7 whose heat treatment temperature satisfied 400 to 600 degrees, the initial resistance value was more excellent than that of the positive electrode active materials of Reference Examples 1 and 2 prepared under heat treatment conditions outside the range.

[0119]

Table 2

[0120]

[0121]

[0122] The present invention can be implemented in various different ways and is not limited to the above-mentioned embodiments. It will be appreciated by those skilled in the art that the present invention can be implemented in other specific ways without changing the technical concept or essential features of the present invention. Therefore, the above-mentioned embodiments are exemplary in all aspects and are not restrictive.

Claims

1. A positive electrode active material, comprising: a lithium metal oxide; and a coating located on the surface of the lithium metal oxide, The coating comprises a first compound, which has a wavelength of 1580 cm -1 Up to 1600cm -1 A peak value is observed in the range, and the average transmittance of the peak value is 0.990 to 0.998, in, The coating further comprises a second compound, which has a wavelength of 1070 cm -1 Up to 1120cm -1 A peak value was observed in the range of 0.985 to 0.993, wherein, when the value obtained by dividing the average absorbance of the first compound by the average absorbance of the second compound is defined as A, A satisfies the following formula 1, [Formula 1] 0.72 > A = (average absorbance of the first compound) / (average absorbance of the second compound) > 0.41 In Formula 1, the absorbance of the first compound is 1 - the transmittance value of the first compound, and the absorbance of the second compound is 1 - the transmittance value of the second compound. wherein the lithium metal oxide is represented by the following Chemical Formula 1: [Chemical Formula 1] Li x Ni a Co b Mr c M1 d M2 e O2 In Chemical Formula 1, M1 and M2 are each at least one of Zr, Ti, Mg, Al, Ni, Mn, Zn, Fe, Cr, Mo, and W, x is 0.90 ≤ x ≤ 1.07, a is 0.80 ≤ a < 1, b is 0 < b ≤ 0.3, c is 0 < c ≤ 0.3, d is 0 < d < 0.01, e is 0 < e < 0.01, and a + b + c + d + e = 1.

2. The positive electrode active material according to claim 1, wherein the first compound is a compound having a CN bond.

3. The positive electrode active material according to claim 1, wherein the second compound is a compound having a SOx bond.

4. The positive electrode active material according to claim 1, wherein in the spectrum detected by X-ray photoelectron spectroscopy (XPS) of the coating, peaks are observed in at least one of the ranges of 398 eV to 404 eV, 166 eV to 173 eV, and 158 eV to 166 eV.

5. The positive electrode active material according to claim 1, wherein the content of nickel in the metals within the lithium metal oxide is 80 mol% or more.

6. A method for preparing a positive electrode active material, comprising: a step of preparing a lithium metal oxide; and a step of forming a coating on the surface of the lithium metal oxide, The coating comprises a first compound, which has a wavelength of 1580 cm -1 Up to 1600cm -1 A peak value is observed in the range, and the average transmittance of the peak value is 0.990 to 0.998, in, the step of forming the coating includes a step of washing the lithium metal oxide with water, the washing step is performed with a washing solution, and the washing solution contains an additive for forming the coating and water, wherein the additive is at least one of ammonium sulfate, ammonium cobalt sulfate hexahydrate, ammonium nickel sulfate, ammonium manganese sulfate, and ammonium aluminum sulfate, wherein the lithium metal oxide is represented by the following Chemical Formula 1: [Chemical Formula 1] Li x Ni a Co b Mr c M1 d M2 e O2 In Chemical Formula 1, M1 and M2 are each at least one of Zr, Ti, Mg, Al, Ni, Mn, Zn, Fe, Cr, Mo, and W, x is 0.90 ≤ x ≤ 1.07, a is 0.80 ≤ a < 1, b is 0 < b ≤ 0.3, c is 0 < c ≤ 0.3, d is 0 < d < 0.01, e is 0 < e < 0.01, and a + b + c + d + e = 1, wherein, based on the washing solution, the content of the additive is 1 wt% to 7 wt%, and After the water washing step, the preparation method further comprises a step of drying the washed lithium metal oxide and then performing a heat treatment step, wherein the heat treatment step is performed at a temperature range of 400° C. to 600° C. for 3 to 10 hours.

7. A lithium secondary battery comprising: A positive electrode comprising the positive electrode active material according to any one of claims 1 to 5; a negative electrode comprising a negative electrode active material; and An electrolyte is located between the positive electrode and the negative electrode.

Citation Information

Patent Citations

  • Lithium transition metal compound oxide powder for lithium secondary battery positive electrode active material and its manufacturing method, its precursor and its manufacturing method, lithium secondary battery positive electrode using it, and lithium secondary battery

    JP2005276502A

  • Positive active material, positive electrode, and lithium battery including the same and method of manufacture thereof

    US20150243970A1